Un indice dell’Evangelo d’oro di Dabra Libānos (Šemazānā, Akkala Guzāy, Eritrea) - Bausi, Alessandro (Aethiopica, 2007)
The present index considers all the proper names and noteworthy terms occurring in the feudal acts published in 1901 by C. Conti Rossini from the Golden Gospel of Dabra Libānos (Šemazānā, Akkala Guzāy, Eritrea). The index is intended as a simple working tool for all those (historians, philologists, linguists, etc.) who may be interested in retrieving informations preserved in the oldest ‘archival’ documentary source of Ethiopia and Eritrea. It preludes to a new edition of the feudal acts furnished with translation and commentary.